Prevalence of oral mucosal lesions in nursing homes elderly people in western Iran - Neda Omidpanah; Fateme Mohamadinejad; Roya Safari faramani (Elsevier, 2021)
Objective: The aim of this study to determine the prevalence of oral mucosal lesions in the elderly living in nursing homes in western Iran (Kermanshah). Background: This study was conducted in the elderly living in nursing homes in Kermanshah, western Iran. Materials and methods: This descriptive study was performed on 598 elderly people who lived in nursing home. Medical history, medication and demographic information were collected from the participants' medical records. This was performed through interview and examination to the instruction explained WHO. Results: A total of 598 elderly, 253 men and 345 women, were examined. Of all the elderly, 101 (16.9%) were smokers and 248 (41.5%) had dentures. The overall prevalence of lesions in the elderly was 52.5%. The most prevalent lesions in the population were xerostomia (37.6%), sublingual varicosity (25.8%), candidiasis (5%), and red and white lesions (4.7%). The most common systemic conditions in the population were hypertension (20.1%), depression (14.2%), and diabetes (6.2%). The elderly with hypertension were 1.743 times more likely to have oral lesions (Odds Ratio = 1.7; confidence interval = 1.15-2.63). Conclusion: Considering the observed oral manifestations and also the nature of aging and its consequent systemic conditions and the side effects of medications and other treatments, the elderly require carefully planned oral and dental health monitoring and care services with special consideration of their conditions.